Self Confidence and Social Identity Relate to Peer Conformity Patterns: Kepercayaan Diri dan Identitas Sosial Berkaitan dengan Pola Konformitas Teman Sebaya - Lisa Nur Aini; Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Adolescence is a transitional developmental stage characterized by significant social, emotional, and cognitive changes, where peer relationships become central in shaping behavioral patterns. Specific Background: Peer conformity represents behavioral and attitudinal adjustment to group norms, while self-confidence and social identity are psychological factors associated with adolescents’ ability to regulate social adaptation and group affiliation. Knowledge Gap: Empirical studies examining the simultaneous relationship between self-confidence, social identity, and peer conformity among junior high school students in Indonesian educational settings remain limited. Aims: This study aimed to analyze the relationship between self-confidence and social identity with peer conformity among students at SMP Negeri 2 Tanggulangin. Results: This quantitative correlational study involved 265 students selected using random sampling. Data were collected using validated Likert scales measuring self-confidence, social identity, and peer conformity, with reliability coefficients of 0.824, 0.799, and 0.906, respectively. Product Moment Pearson correlation and multiple correlation analysis revealed a significant relationship between self-confidence and social identity with peer conformity, with a multiple correlation coefficient of R = 0.501 and significance level F Change < 0.05. The findings indicated a negative relationship, showing that higher levels of self-confidence and social identity were associated with lower peer conformity. Most participants were categorized in moderate levels across the three variables. Novelty: This study provides quantitative evidence demonstrating the combined relationship between self-confidence, social identity, and peer conformity among Indonesian junior high school adolescents. Implications: The findings highlight the importance of developing psychological and social identity competencies within school-based guidance programs to support adolescents’ adaptive social behavior. Highlights: Higher Psychological Assurance Corresponds With Reduced Adjustment to Group Behavioral Pressure. Strong Group Affiliation Demonstrates an Inverse Association With Behavioral Adaptation to Peers. Majority of Participants Demonstrated Moderate Levels Across Measured Psychosocial Variables. Keywords: Peer Conformity, Self Confidence, Social Identity, Adolescents, Correlational Study